The Popular Phenomenon Of Abandoned Street Children In Big Cities In Indonesia - Khamim Zarkasih Putro; Yuyun Ayu Lestari (JOYCED: Journal of Early Childhood Education, 2021)
Children as social beings who have the right to grow and develop and live freely and play according to their age without feeling uncomfortable. In big cities there are still many children who are forced to take to the streets and help their parents earn a living, regardless of their needs, healt, rights and risks. The purpose of this study is to find and explain the factors for the emergence of street children, the risks that can be obtained when children take to the streets, obstacles and efforts to handle the rise of street children. The method used in this research is the library research method which collects data or information through reviewing and exploring several printed and online references. The result is that the government had made efforts in handling and eradicating case of street children, Such as the construction of foster homes, community empowerment and other handling.